The Influence of Customer Satisfaction and Trust on Loyalty at Indonesian Shariah Bank - Ni'mati Rahmatika, Arivatu; Apriadi, Dede (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2024)
The purpose of this study is to determine the effect of customer satisfaction on the loyalty of Bank Syariah Indonesia KC Jombang Cempaka Mas. The subject of this study is the loyalty of Bank Syariah Indonesia KC Jombang Cempaka Mas and the goal is customer satisfaction and trust. The location of this study is Jombang Regency. This positioning is assessed based on the influence of customer satisfaction and trust on bank loyalty. Therefore, the author is interested in conducting further research on the level of customer satisfaction and trust in bank loyalty. The sampling method is non-probability sampling and data collection is carried out by purposive sampling. Data was collected using questionnaires sampled by 100 respondents. The type of research in this study is quantitative descriptive research using multiple regression analysis, coefficient of determination, and subtests (T-test). The results of this study show that several satisfaction variables (X1) and trust variables (X2) partially (T-test) have a positive and significant influence on the loyalty of Bank Syariah Indonesia KC Jombang Cempaka Mas (Y) which shows that there is an Adjusted R-squared produced is 74.9% and the remaining 25.1% is influenced by other variables.